Flexural Performance of Concrete Beams Strengthened Using CFRP Sheets with Large Spike Anchors - Assad, Maha A. (2023)
A Master of Science thesis in Civil Engineering by Maha A. Assad entitled, “Flexural Performance of Concrete Beams Strengthened Using CFRP Sheets with Large Spike Anchors”, submitted in March 2023. Thesis advisor is Dr. Rami Haweeleh and thesis co-advisor is Dr. Jamal Abdalla. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).